2005
DOI: 10.1021/jf0508549
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Dough Proofing Conditions To Enhance Isoflavone Aglycones in Soy Bread

Abstract: Native beta-glucosidase activity in soy bread can convert isoflavone glucosides to aglycones during proofing, and this study determined the time-temperature dependence of this process. Samples were taken every hour for 4 h during proofing at 22, 32, and 48 degrees C to determine beta-glucosidase activity and isoflavone profiles of the dough. After 1-2 h, the beta-glucosidase activity increased 43-84% achieving a plateau value at 22 degrees C but declining when proofed beyond 2 h at 32 degrees C and 48 degrees … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…The external environment variations such as heat, acid, alkaline, and enzymes can accelerate the inter-conversion reactions of isoflavones. [18] The daidzin, genistin, and glycitin amount in the current research was found to be increased. A previous study showed a conversion between isoflavones from malonyl derivatives to actetyl derivatives and β-glucosides after roasting.…”
Section: Isoflavone Of Raw and Roasted Soybeansmentioning
confidence: 44%
“…The external environment variations such as heat, acid, alkaline, and enzymes can accelerate the inter-conversion reactions of isoflavones. [18] The daidzin, genistin, and glycitin amount in the current research was found to be increased. A previous study showed a conversion between isoflavones from malonyl derivatives to actetyl derivatives and β-glucosides after roasting.…”
Section: Isoflavone Of Raw and Roasted Soybeansmentioning
confidence: 44%
“…Further studies are needed to elucidate the nature of groundnut isoflavones, including changes in the content of genistein-7-O-genitiobioside in groundnuts during crop growth. Given the previous findings in soybeans revealing that their isoflavone composition varies depending on the processing methods (Grün et al, 2001;Riedl, Zhang, Schwartz, & Vodovotz, 2005;Yin, Li, Liu, Saito, & Tatsumi, 2005), along with the potential of groundnuts as an important isoflavone source, the effects of processing methods and storage conditions on the groundnut isoflavone composition also merit further research. Moreover, further analysis is required to determine the molecular structures of other components (peaks) isolated from the groundnut extract along with peak-1.…”
Section: Resultsmentioning
confidence: 99%
“…The endogenous b-glucosidase activity in soybean can convert isoflavone to aglycones during proofing. The level of malonyl glycosides decreased 3-15% whereas that of acetyl glycosides was fairly constant (Riedl et al, 2005). Most commonly, previous studies suggest that the unstable malonyl glycosides can easily be transformed into less conjugated forms by a thermal process (Barbosa et al, 2006;Coward et al, 1998).…”
Section: Soybean Glycosidementioning
confidence: 95%
“…Soybean isoflavones have attracted considerable attention for their health benefits in the prevention of cancer, osteoporosis, postmenopausal syndromes and hypercholesterolaemia (Nielsen & Williamson, 2007;Setchell et al, 2002). The content and composition of these isoflavones vary in soybean foods, depending on the soybean varieties and processing techniques, such as heat treatment and fermentation (Anderson & Wolf, 1995;Barbosa, Lajolo, & Genovese, 2006;Chun, Kim, & Kim, 2008;Coward, Smith, Kirk, & Barnes, 1998;Riedl, Zhang, Schwartz, & Vodovotz, 2005;Yamabe, Kobayashi-Hattori, Kaneko, Endo, & Takita, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation